STATUS KEWARISAN ISLAM ANAK LUAR NIKAH: Pasca Putusan Mahkamah Konstitusi No.46/PUU-VIII/2010 - Habibah, Habibah (Moderation | Journal of Islamic Studies Review, 2021)
Abstract:. The problem in this research is, how is the law of Islamic inheritance on children born outside of marriage after the decision of the Constitutional Court of the Republic of Indonesia (MKRI) Number 46 / PUU-VIII / 2010, and how is the impact of the decision of the Constitutional Court of the Republic of Indonesia (MKRI) Number 46 / PUU -VIII / 2010 for the recognition of children out of wedlock against the law of inheritance. This type of research uses a research library, the data collected is then processed through qualitative methods and analyzed using deductive thinking that draws specific conclusions. The results obtained in this study include the Constitutional Court's decision when we review from Islamic law, so children born out of wedlock only have a civil relationship with the mother and mother's family and the positive impact of this Constitutional Court decision is the existence of a family relationship between the child outside marriage and the biological father. Meanwhile, the negative impact is that with this Constitutional Court decision, it is the responsibility of the parents to have children born from sirri marriages.